Defy me - Mafi, Tahereh (Mafi, Tahereh. Shatter me series., 2020)
"Juliette Ferrars isn't who she thinks she is. Nothing in her world is what it seemed. She thought she'd finally defeated the Reestablishment. She thought she'd finally taken control of her life, her power, and her pain. But Juliette has only just begun to unravel a lifetime of lies, and she finds herself faced with a familiar choice: Be a weapon. Or be a warrior. This time, she's not alone. Stronger, braver, and more resilient than ever, Juliette will fight for life and love with her friends by her side--but first, she has to survive the war being waged against her mind: She has to remember who she was"--Provided by publisher.